Peningkatan Kepercayaan Konsumen E-Commerce di Provinsi Sumatera Utara Melalui Teknologi Informasi - Ibrahim Syahputra Harahap; Muhammad Irwan Padli Nasution (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This study aims to determine the level of trust of the people of North Sumatra in making online purchases or often referred to as e-commerce. This research uses descriptive quantitative research using a survey approach. Distribution of questionnaires through the Google From application, with 53 respondents. Questions are carried out using a Likert scale. The results showed that 50 people believed in e-commerce by 94.3%, who did not believe in the existence of E-Commerce3 people or equivalent to 5.7%. Related to this aspect of trust that the people of North Sumatra often do e-commerce as a place to meet needs easily and practically and can be done anywhere.